2023
DOI: 10.3389/fnins.2023.1301515
|View full text |Cite
|
Sign up to set email alerts
|

Deschloroclozapine exhibits an exquisite agonistic effect at lower concentration compared to clozapine-N-oxide in hM3Dq expressing chemogenetically modified rats

Makiko Shimizu,
Mitsuhiro Yoshimura,
Kazuhiko Baba
et al.

Abstract: IntroductionWithin the realm of chemogenetics, a particular form of agonists targeting designer receptors exclusively activated by designer drugs (DREADDs) has emerged. Deschloroclozapine (DCZ), a recently introduced DREADDs agonist, demonstrates remarkable potency in activating targeted neurons at a lower dosage compared to clozapine-N-oxide (CNO).MethodsWe conducted a comparative analysis of the effects of subcutaneously administered CNO (1 mg/kg) and DCZ (0.1 mg/kg) in our transgenic rats expressing hM3Dq a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Conversely, inhibition of Gi-DREADD (hM4Di) expressing CeA-KOR neurons resulted in hyperpolarization and decreased action potential firing (Figure 4(D3-D6)). Future studies can build on these findings to achieve temporal control over specific neuronal activation or inhibition with the administration of the normally pharmacologically inert ligand DCZ [58,59], allowing for a more detailed investigation of the dynamic role of CeA-KOR neurons in pain-related processing. The chemogenetic approach is both repeatable and reversible [60,61], facilitating the longitudinal study of CeA-KOR activation/inactivation on chronic pain-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of Gi-DREADD (hM4Di) expressing CeA-KOR neurons resulted in hyperpolarization and decreased action potential firing (Figure 4(D3-D6)). Future studies can build on these findings to achieve temporal control over specific neuronal activation or inhibition with the administration of the normally pharmacologically inert ligand DCZ [58,59], allowing for a more detailed investigation of the dynamic role of CeA-KOR neurons in pain-related processing. The chemogenetic approach is both repeatable and reversible [60,61], facilitating the longitudinal study of CeA-KOR activation/inactivation on chronic pain-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, its pharmacokinetics indicate that the DCZ concentrations in the plasma and brain decrease significantly within two hours post- injection, and it is metabolized into C21 and DCZ-N-oxide. Some studies have reported equivalent or superior results with DCZ compared to other actuators (Ferrari et al, 2022; Nentwig et al, 2022; Shimizu et al, 2023). Therefore, DCZ could be a useful alternative worth considering in future research.…”
Section: Discussionmentioning
confidence: 99%